2017
DOI: 10.4315/0362-028x.jfp-17-180
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Salmonella and Shiga Toxin–Producing Escherichia coli in Lymph Nodes of Australian Beef Cattle

Abstract: Salmonella contamination of ground beef has been viewed as originating from the surface of carcasses. Recent studies have identified lymph nodes as a potential source of Salmonella contamination because these tissues play an active role in containment of pathogens in the live animal and because some lymph nodes are unavoidably present in manufacturing beef trimmings or primal cuts that may be incorporated into ground beef. A survey was conducted of the microbiological status of lymph nodes from Australian catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…According to recent investigations, lymph nodes are recognised as a potential reservoir of Salmonella, not only because of their active role in the containment of pathogens in animals, but also as a result of their unavoidable presence on carcasses during the trimming process at abattoirs [112]. A recent study of 1464 lymph nodes randomly selected from chilled cattle carcasses in five processing facilities in different Australian states (QLD, NSW, VIC, TAS and SA) found a low carriage of Salmonella (0.48%) amongst tested samples, with S. Typhimurium and S. Virchow being the predominant serovars [112]. Salmonella spp.…”
Section: Multi-statesmentioning
confidence: 99%
“…According to recent investigations, lymph nodes are recognised as a potential reservoir of Salmonella, not only because of their active role in the containment of pathogens in animals, but also as a result of their unavoidable presence on carcasses during the trimming process at abattoirs [112]. A recent study of 1464 lymph nodes randomly selected from chilled cattle carcasses in five processing facilities in different Australian states (QLD, NSW, VIC, TAS and SA) found a low carriage of Salmonella (0.48%) amongst tested samples, with S. Typhimurium and S. Virchow being the predominant serovars [112]. Salmonella spp.…”
Section: Multi-statesmentioning
confidence: 99%
“…Numerous studies have reported relatively low prevalence of Salmonella isolated from lymph nodes in cattle (Arthur et al, 2008; Bailey et al, 2017; Smith et al, 2021; Webb et al, 2017). Results from the current study support these findings as the average Salmonella prevalence isolated from lymph nodes was 8.4% (0.0–14.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pathogenic E. coli are responsible for approximately 205,000 infections, 2500 hospitalizations and 20 deaths per year in the United States (Scallan et al, 2011). Both Salmonella and E. coli can contaminate carcasses from hides during processing; however, Salmonella is also able to colonize the lymphatic system and contaminate ground beef via trimmings (Arthur et al, 2008; Bailey, Huynh, Govenlock, Jordan, & Jenson, 2017). Therefore, the objective of this study was to investigate the link between concentrations of antimicrobial‐resistant Salmonella , Enterococcus and E. coli resulting from common metaphylactic antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the studies conducted on carcass lymph nodes have shown that those nodes may harbor pathogenic microorganisms such as Salmonella spp. (4). It is known that completely removing lymph nodes from the carcass is impossible.…”
Section: Introductionmentioning
confidence: 99%